Metabolic and Metabolomic Insights Regarding the Omega-3 PUFAs Intake in Type 1 Diabetes Mellitus - Purdel, Carmen; Ungurianu, Anca; Margina, Denisa (Frontiers in Molecular Biosciences, 2021)
Type 1 diabetes mellitus (T1DM) is currently considered an autoimmune disease characterized by the destruction of pancreatic β-cells, insulin deficiency, and dysglycemia. Dietary factors, including omega-3 polyunsaturated fatty acids (ω-3 PUFAs), were reported to influence T1DM. Therefore, a better understanding of the potential role of ω-3 PUFAs in the development and progression of T1DM will help to improve the clinical management of the disease. In this review, we explored the current understanding of molecular mechanisms and signaling pathways induced by ω-3 PUFAs and the beneficial effects of ω-3 PUFAs intake in the prevention and treatment of T1DM, as well as the underlying possible metabolomic (lipidomics) changes.